2020
DOI: 10.1002/epi4.12433
|View full text |Cite
|
Sign up to set email alerts
|

Complete hemispherotomy leads to lateralized functional organization and lower level of consciousness in the isolated hemisphere

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…RSFC analysis in this patient with remarkable clinical recovery 6 years after near-complete loss of the right hemisphere indicates increased between-network connectivity for all seven networks examined in the preserved (dominant) hemisphere. This is numerically consistent with two recent reports of eight patients who had surgical hemispherectomy in childhood (2,3). This suggests that a shift toward increased between-network connectivity can be observed not only following childhood surgical hemispherectomy due to epilepsy, but also in an adult patient within a few years after functional hemispherectomy due to ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…RSFC analysis in this patient with remarkable clinical recovery 6 years after near-complete loss of the right hemisphere indicates increased between-network connectivity for all seven networks examined in the preserved (dominant) hemisphere. This is numerically consistent with two recent reports of eight patients who had surgical hemispherectomy in childhood (2,3). This suggests that a shift toward increased between-network connectivity can be observed not only following childhood surgical hemispherectomy due to epilepsy, but also in an adult patient within a few years after functional hemispherectomy due to ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study in six adults who underwent surgical hemispherectomy during childhood for intractable epilepsy reported that RSFC within seven brain networks was generally intact in the preserved hemisphere, but RSFC between networks was substantively increased compared to healthy controls (2). Moreover, increased contralateral and inter-hemispheric connectivity have been reported in a previous study employing rs-fMRI in complete surgical hemispherotomy, including total callosotomy with a perithalamic section, in two children (3). This suggests that hemispherectomy results in a strengthening of preserved inter-network connectivity, despite major structural disruptions, and shows that rs-fMRI can inform alterations in brain function in patients after hemispherectomy in childhood.…”
Section: Introductionmentioning
confidence: 90%
“…All patients had preoperative MRI and postoperative MRI at day 1, day 10 (detection of hydrocephalus), and after 3 months, with a protocol including at least 3DT1, 3DT2, and diffusion-weighted MRI sequences, along perfusion imaging with arterial spin labeling and bold fMRI as previously reported. 10…”
Section: Methodsmentioning
confidence: 99%
“…8,9 We followed this technique during the past decade in our institution and reported preliminary results of both the seizure outcome and the functional postoperative reorganization of the healthy hemisphere. 10 The aim of the study is to describe in a large cohort from two centers the surgical steps with video support, to analyze the seizures' outcome and complications of the procedure, and to report failures and limitations of this approach considering systematic postoperative MRI imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation